A protocol for measuring the direct effect of cycling on neuromuscular control of running in triathletes - Chapman, A. R.; Vicenzino, B.; Hodges, P. W.; Blanch, P.; Hahn, A. G.; Milner, T. E. (Journal of Sports Sciences, 2009)
The direct effects of cycling on movement and muscle recruitment patterns (neuromuscular control) during running are unknown but critical to success in triathlon. We outline and test a new protocol for investigating the direct influence of cycling on neuromuscular control during running. Leg movement (three-dimensional kinematics) and muscle recruitment (surface electromyography, EMG) were compared between a control run (no prior exercise) and a 30-min transition run that was preceded by 20 min of cycling. We conducted three experiments investigating: (a) the repeatability (between-day reliability) of the protocol; (b) the ability of the protocol to investigate, in highly trained national or international triathletes, the direct influence of cycling on neuromuscular control during running independent of neuromuscular fatigue; and (c) the ability of the protocol to provide a control, or baseline, measure of neuromuscular control (determined using a measure of stability) without causing fatigue. Kinematic and EMG measures of neuromuscular control during running showed moderate to high repeatability: mean coefficients of multiple correlation for repeatability of EMG and kinematics were 0.816 ± 0.014 and 0.911 ± 0.031, respectively. The protocol provided a robust baseline measure of neuromuscular control during running without causing neuromuscular fatigue (coefficients of multiple correlation for stability of EMG and kinematics were 0.827 ± 0.023 and 0.862 ± 0.054), while EMG and force data provided no evidence of fatigue. The protocol outlined here is repeatable and can be used to measure any direct influence of cycling on neuromuscular control during running.